Gamification and the development of socio-emotional skills in the classroom (Research, Society and Development, 2021)
The communicative demands of the 21st century is characterized by new technological resources that shape human expressions that are increasingly biased by the enormous informational flow generated by globalizing processes. In this context, there is the young people that, increasingly resignifying new forms of communication, requires new ways of learning. From gamification, social-emotional skills can be developed in the classroom, given that, in the gamification process, the student finds himself in situations where he needs to know how to deal with himself, with the other and with the proposed challenges. As a problem of this research, the question is: what pedagogical gamification strategy can be used for the development of a more significant learning in individuals who build themselves socio-emotionally competent? For this, the objective is to theoretically review the notions about gamification, socio-emotional skills and a responsive and responsible subject, so that it is possible, then, to propose a teaching-learning development strategy based on gamification, through a careful look at development of students' socio-emotional skills. Through a bibliographical, exploratory, qualitative and propositional methodology, this research is based on studies on 1) socio-emotional skills (Del Prette & Del Prette, 2001; Pena, Alves, Primi, 2020); 2) gamification and teaching-learning; and 3) the dialogic-discursive interaction of the responsive and responsible individual (Bakhtin, 2010, 2016). Reflections on the new challenges of teaching and learning today are considered fruitful, through a collaborative pedagogical strategy that raises mental strengthening and socio-emotional development in an interactive activity of active understandings.